ANALISIS KLASIFIKASI BIAYA DAN IMPLIKASINYA TERHADAP PERENCANAAN DAN PENGENDALIAN STRATEGIK: STUDI KASUS WARUNG POJOK - Daffa Falih Syahbana; Rizkyka Delo Octaviana; Muhammad Ammar Kahfi (CV. Denasya Smart Publisher, 2026)
This research intends to examine how costs are categorized and their effects on strategic planning and management at Warung Pojok GG. Hj. Gumat III, which operates as a small business in the food industry. This study employed a descriptive qualitative method with a case study approach. Information was gathered through interviews, firsthand observations, and basic documentation pertaining to sales, operating expenses, and financial planning. The results show that the cost structure for Warung Pojok heavily relies on variable costs, particularly those related to raw materials, which are affected by the volume of sales and operations. An analysis of sales indicates that instant noodles and ready-to-eat meals are the key contributors to the establishment's revenue. The difference between projected budgets and actual spending indicates negative variances, primarily due to rising prices for raw materials and utility costs. Despite not having a formal accounting system in place, the use of straightforward cost classification enables the owner to grasp cost dynamics, enhance operational planning, assist in managing costs, and bolster strategic choices to ensure efficiency and the long-term viability of the business.